The Formation of Entrepreneurial Competencies in the Modern Russian School - Mariia KONIAGINA (Communications of International Proceedings, 2021)
In the conditions of the emerging market, there is a need to form a number of entrepreneurs who would help to ensure the growth of the national economy. The work explores the quality of the formation of an entrepreneur's personality and his basic competencies at the level of general literacy, which is developing in a secondary school. The aim of the study is to assess the basic competencies level of the Russians required in entrepreneurial activity and the adequacy of their self-esteem for a successful business. Several steps were made: - A survey was conducted of respondents who gave a subjective assessment of their general literacy and basic competencies useful for entrepreneurial activity. - Provided a comparative analysis, which studies of the literacy level of Russians and residents of the developed countries were systematized. - Identified the problems of the entrepreneurial competencies’ formation in Russia. - Some solutions have been proposed to improve the work on the basic entrepreneurial soft skills formation of Russians. The presented study made it possible to reveal the discrepancy between the real and the expected level of basic entrepreneurial competencies in Russia. Young Russians rather quickly lose their desire to do business, blaming the responsibility for this on the secondary school, which, in their opinion, does not form competencies for this. A sobering conclusion is that the literacy level of Russians, forming basic entrepreneurial competencies, has significantly decreased over the past few decades and does not correlate with the well-being of citizens.
Keywords: Literacy; Entrepreneurial Competencies; Entrepreneurial Education; School